Analisis Hasil Perhitungan Harga Pokok Produksi Metode Full Costing Vs Variabel Costing pada UMKM BMS Kota Gorontalo - Valentina Monoarfa; Yuliana Lepa; Dinarova Salsavia Datau (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Calculating the cost of production is very important for manufacturing companies considering that one of the benefits of the cost of production is determining the selling price of the product. There are two methods for determining the cost of production, namely the full costing method and the variable costing method. This research aims to determine the calculation of the cost of production of BMS MSMEs using the full costing and variable costing methods. The method in this research is the Quantitative Descriptive method. The data collection technique for this research is by observation/interview. The problem in this research is to compare the calculation of product cost with full costing and variable costing methods. The purpose of this research is to determine the determination of the cost of production based on the method used by the company, namely the full costing and variable costing methods. The results of the research obtained the cost of production using the full costing method of Tapi. 667.77, while with the variable costing method it is Rp. 334.44. The conclusion from this research is that there are differences in determining the cost of products using these two methods.